The application of genetic testing technology in kidney transplantation: precision matching, non-invasive monitoring and personalized management - Zhang, Yalong; Wang, Hao; Yan, Rui; Wang, Kangyu; Man, Jiangwei; Yang, Li (Frontiers in Immunology, 2026)
Kidney transplantation remains the treatment of choice for patients with end-stage renal disease, yet its long-term success continues to face major challenges, including organ shortage, rejection, and drug toxicity. With the advancement of genetic testing technologies, transplant management is progressively shifting from empirical practice toward precision medicine. This review systematically outlines four core applications of genetic testing in kidney transplantation: from pre-transplant precision donor-recipient matching and risk stratification, to peri-operative pharmacogenomics-guided immunosuppression, and finally post-transplant noninvasive rejection monitoring and infection management. By integrating high-resolution HLA typing, epitope mismatch analysis, donor-derived cell-free DNA monitoring, urinary biomarker detection, genotyping of drug-metabolizing genes such as CYP3A5, and assessment of host susceptibility variants, genetic technologies have significantly improved transplant outcomes. Despite persistent challenges in standardization, clinical translation, and ethical considerations, emerging innovations including microfluidics, nanopore sequencing, and organoid modeling are expected to further accelerate the transition of kidney transplantation into a new era of comprehensive precision management.